Targeted therapies in the treatment of germ cell tumors: The need for new approaches against “orphan” tumors - Sánchez-Muñoz, Alfonso; Jiménez-Rodríguez, Begoña; Navarro-Pérez, Víctor; Medina-Rodríguez, Laura; Llácer, Casilda; Vicioso-Recio, Luis Prudencio; Machuca, Javier; Alba-Conejo, Emilio (Elsevier Ireland Ltd, 2012)
Germ cell tumors (GCTs) are a heterogeneous group of tumors that are highly clinically relevant to oncologists. GCTs are generally highly sensitive to cisplatin-based chemotherapy and represent a model for curable neoplasms. Cisplatin-based combination therapy followed by surgical resection of the residual tumor is the cornerstone for GCTs treatment. Although the overall cure rate is high for patients with GCTs, patients with a poor prognosis according to International Consensus Criteria or with chemoresistant disease remain a major clinical challenge. Currently, between 15% and 20% of patients with metastatic disease still progress and will die as a consequence of the disease. Therefore, the discovery of new treatment strategies or new drugs based on translational oncology remains a priority for the treatment of patients with cisplatin-refractory disease and those with a poor prognosis. Clinical trials with new targeted therapies are ongoing for the treatment of GCTs. In this article, we review some of the new targeted biologic therapies that act on the most relevant oncogenesis pathways and are in clinical development for the treatment of GCTs
Este artículo ha sido publicado en la revista Critical Reviews in Oncology/Hematology Esta versión tiene Licencia Creative Commons CC-BY-NC-ND
Keywords: Testículos - Cáncer - Tratamiento; Targeted therapy; Germ cell tumors; Testicular tumors